A hairpin DNA-fueled nanoflare for simultaneous illumination of two microRNAs in drug-induced nephrotoxic cells with target catalytic recycling amplification. Issue 24 (24th October 2019) - Gao, Han; Li, Jiwei; Jia, Yuran; Yu, Xie-an; Qi, Jin; Tian, Jiangwei; Yu, Bo-Yang
Abstract : A hairpin DNA-fueled nanoflare for the simultaneous and sensitive detection of two drug-induced nephrotoxicity-related miRNAs with target catalytic recycling amplification. Abstract : The detection of specific extracellular microRNAs (miRNAs) is beneficial for the prediction of drug-induced kidney injury. Here, a novel hairpin DNA-fueled nanoflare was developed for the simultaneous detection of drug-induced nephrotoxicity-related miRNA-21 and miRNA-200c with target catalytic recycling amplification. The nanoflare utilized gold nanoparticles (AuNPs) as the highly efficient quencher to ensure a low background signal. With the help of the fueled hairpin DNA, the miRNA targets could serve as the catalysts for the assembly of DNA duplexes. Therefore, the nanoflare could respond to the miRNAs to yield signal outputs of 1 :  n (target : signal) rather than an equivalent reaction ratio of 1 : 1, achieving the signal amplified detection of low-abundant miRNAs. The targets can be concurrently detected with the detection limit of 18.1 and 21.1 pM for miRNA-21 and miRNA-200c, respectively, which are approximately 2 orders of magnitude lower than that of the non-catalytic probes. In addition, this nanoflare offered a high selectivity for determination between perfectly matched targets and single-base mismatched targets. It should be noted that the nanoflare was successfully employed to predict the drug-induced nephrotoxicity by the detection of miRNAs in culture media excreted from the drug-treated renal cells using a fluorescent microplate reader. Our hairpin DNA-fueled nanoflare could also accurately detect the divergence of miRNA-21 and miRNA-200c between drug-treated nephrotoxic cells and tumor cells, demonstrating a promising potential for exploring the pathogenesis of drugs and auxiliary diagnosis of drug-induced nephrotoxicity.